2006
DOI: 10.1002/em.20274
|View full text |Cite
|
Sign up to set email alerts
|

Influence of polymorphisms at loci encoding DNA repair proteins on cancer susceptibility and G2chromosomal radiosensitivity

Abstract: Sixteen candidate polymorphisms (13 SNPs and 3 microsatellites) in nine genes from four DNA repair pathways were examined in 83 subjects, comprising 23 survivors of childhood cancer, their 23 partners, and 37 offspring, all of whom had previously been studied for G 2 chromosomal radiosensitivity. Genotype at the Asp148Glu SNP site in the APEX gene of the base excision repair (BER) pathway was associated with childhood cancer in survivors (P = 0.001, significant even after multiple test adjustment), due to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 53 publications
0
17
1
Order By: Relevance
“…28 Another study showed that rs861539 was associated with G2 chromosomal radiosensitivity and could have a protective role in cancer susceptibility. 29 However, the same group 4 years later failed to repeat their previous data on the association between rs861539 and cancer risk or G(2) chromosomal radiosensitivity. 30 Meta-analysis 19,31 studies concluded that this SNP might have not been associated with lung cancer risk.…”
Section: Discussionmentioning
confidence: 98%
“…28 Another study showed that rs861539 was associated with G2 chromosomal radiosensitivity and could have a protective role in cancer susceptibility. 29 However, the same group 4 years later failed to repeat their previous data on the association between rs861539 and cancer risk or G(2) chromosomal radiosensitivity. 30 Meta-analysis 19,31 studies concluded that this SNP might have not been associated with lung cancer risk.…”
Section: Discussionmentioning
confidence: 98%
“…Assays that have shown promise include colony survival assays (Brock et al, 1995;West et al, 1998), chromosomal aberration frequency (Neubauer et al, 1997(Neubauer et al, , 2002Distel et al, 2006), comet assay (Brammer et al, 2001), DNA damage and repair based on pulsedfield gel electrophoresis (PFGE) (Wurm et al, 1994;McKay and Kefford, 1995;Zhou et al, 1998), micronucleus assay (Nachtrab et al, 1998;Sprung et al, 2005), telomere length (McIlrath et al, 2001;Sprung et al, 2008), SNP analysis (Severin et al, 2001;Gurska et al, 2007;Wilding et al, 2007;Alsner et al, 2008), DNA end binding complexes (Ismail et al, 2004) and transcriptional profiling (Rieger et al, 2004;Svensson et al, 2006;Sprung et al, in preparation). Thus, many potential endpoints exist, most of which have been partially successful in identifying clinical RS.…”
mentioning
confidence: 99%
“…Single-nucleotide polymorphisms (SNPs) in DNA repair genes may alter protein function and individual's capacity to repair damaged DNA, by which influence individual radiosensitivity and the risk of developing radiation-induced toxicities (9). In current view, normal tissue reactions exhibited after RT were determined by a multifactorial trait resulted from the combined effects of clinical, tumor, treatment and genetic factors (10,11).…”
Section: Introductionmentioning
confidence: 99%